Psychological and experiential contributors to experienced cyclists' on-road cycling behaviour: A path analysis study. (February 2023) - Bishop, Daniel T.; Broadbent, David P.; Graham, Anna; Natesan Batley, Prathiba
Highlights: Internal Distraction Control negatively predicted cyclists' errors. It also negatively predicted self-reported violations. Years of cycling positively predicted errors, violations, and negative experiences. Self-efficacy positively predicted violations. Self-efficacy negatively predicted positive behaviours. Abstract: Cyclists' behaviour may be characterised as both positive and negative, although research has typically focused on the latter – notably, behaviours such as crashes, collisions, and errors. Cyclist distraction is often implicated in these negative behaviours. However, there is a dearth of research on the psychological correlates of errant cycling behaviours and distraction. We distributed an online survey that included a combination of established and novel measures to 191 experienced cyclists (155 M, 36 F; aged 18–80 yrs, M age = 57.03 yrs) to ascertain their self-reported cycling behaviour and experience, their attentional style, their cycling self-efficacy and their negative experiences whilst cycling. We conducted path analysis to explore relationships between these variables – specifically, to determine whether self-reported cycling behaviour and negative experiences would be predicted by attentional style, cycling self-efficacy, and cycling experience. Of the statistically significant relationships, Internal Distraction Control negatively predicted cyclists' self-reported errors (b = -0.235) and violations (b = -0.195). The cyclists' years of urban cycling positively predicted their errors (b = 0.068), violations (b = 0.046) and negative experiences (b = 0.05) when cycling. Cycling self-efficacy positively predicted violations (b = 0.003) and negatively predicted positive behaviours (b = -0.002). These results suggest that a combination of psychological and experiential factors explain some of the variance in self-reported cycling behaviours – particularly negative ones. Road user entropy in UK towns and cities is set to increase as micromobility usage increases. Formal assessment of cyclists' capabilities, particularly their ability to deal with distractions, may be crucial to mitigate the consequences.